2018
DOI: 10.1002/jmri.26325
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort echo time imaging for quantification of hepatic iron overload: Comparison of acquisition and fitting methods via simulations, phantoms, and in vivo data

Abstract: Background Current R2*‐MRI techniques for measuring hepatic iron content (HIC) use various acquisition types and fitting models. Purpose To evaluate the accuracy and precision of R2*‐HIC acquisition and fitting methods. Study Type Signal simulations, phantom study, and prospective in vivo cohort. Population In all, 132 patients (58/74 male/female, mean age 17.7 years). Field Strength/Sequence 2D‐multiecho gradient‐echo (GRE) and ultrashort echo time (UTE) acquisitions at 1.5T. Assessment Synthetic MR signals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…Scientific Reports | (2020) 10:17887 | https://doi.org/10.1038/s41598-020-74968-z www.nature.com/scientificreports/ et al43 studied the effect of Rician and non-Rician noise on the accuracy of R2* estimation in 7 different magnitude-based models, and found, the agreement of the R2* estimation was excellent in patients with low ferritin but poor in patients with high ferritin, as expected. Tipirneni-Sajja et al44 simulated 5 different magnitude-based R2* models (GRE-A, GRE-B, GRE-C, UTE-A, and UTE-A), and found, the constant offset monoexponential model overestimated the R2* at the lowest simulated SNR, and the monoexponential fitting with noise subtraction is the most robust and accurate R2* model for ultrashort TE (UTE) sequence.A limitation of the presented work is the narrow age range of the studied group. Therefore, it was not possible to analyze the correlation of R2* with age.…”
mentioning
confidence: 99%
“…Scientific Reports | (2020) 10:17887 | https://doi.org/10.1038/s41598-020-74968-z www.nature.com/scientificreports/ et al43 studied the effect of Rician and non-Rician noise on the accuracy of R2* estimation in 7 different magnitude-based models, and found, the agreement of the R2* estimation was excellent in patients with low ferritin but poor in patients with high ferritin, as expected. Tipirneni-Sajja et al44 simulated 5 different magnitude-based R2* models (GRE-A, GRE-B, GRE-C, UTE-A, and UTE-A), and found, the constant offset monoexponential model overestimated the R2* at the lowest simulated SNR, and the monoexponential fitting with noise subtraction is the most robust and accurate R2* model for ultrashort TE (UTE) sequence.A limitation of the presented work is the narrow age range of the studied group. Therefore, it was not possible to analyze the correlation of R2* with age.…”
mentioning
confidence: 99%
“…Some cases were excluded as failed fit likely due to severe iron overload, which causes the signal to decay rapidly before the first possible TE ~ 1 msec is achieved with our conventional GRE sequence. For these severe iron cases, ultrashort echo time (UTE) sequences (TE 1 ~ 0.1 msec) can be a viable alternative for accurate HIC determination as demonstrated via simulations, phantoms, and patient data 31 . Further, some recent studies have demonstrated implementing QSM with UTE in iron phantoms, 32,33 however studies in patients and in the presence of fat need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For these severe iron cases, ultrashort echo time (UTE) sequences (TE 1 $ 0.1 msec) can be a viable alternative for accurate HIC determination as demonstrated via simulations, phantoms, and patient data. 31 Further, some recent studies have demonstrated implementing QSM with UTE in iron phantoms, 32,33 however studies in patients and in the presence of fat need further investigation.…”
Section: Limitationsmentioning
confidence: 99%
“…Nine cylindrical iron-doped phantoms of 50 mL each were created using 2% agar-water mixtures and iron particles (0.85 μm diameter, MFY0002, MAGNEFY; Bangs Laboratories, Fishers, IN, USA) with varying iron concentrations (0, 0.0075, 0.025, 0.04, 0.06, 0.1, 0.2, 0.4, 0.8%) to cover the clinically relevant R 2 * range. 15,17,19 The phantoms were scanned on a 1.5 T MRI scanner (Avanto, Siemens Healthineers, Malvern, PA, USA) using GRE and UTE acquisitions with the following acquisition parameters. GRE: TE 1 = 1.2 ms, ΔTE = 0.72 ms, TE max = 6.…”
Section: Phantomsmentioning
confidence: 99%
“…13 A previous study in phantoms and patients has shown that both the ARMA and NLSQ models produced inaccurate R 2 * results in some conditions of high iron overload (R 2 * > 500 s À1 ) with and without steatosis, respectively, both methods potentially failing due to rapid R 2 * decay that is not adequately captured with the current Cartesian-based GRE acquisitions with TE 1 of about 1 ms. 11 Alternatively, multiecho ultrashort echo time (UTE) acquisitions use center-out radial sampling that facilitate shorter TE 1 (0.1-0.19 ms) and have been proposed for quantifying severe iron overload and demonstrated to improve the accuracy and precision in R 2 * quantification over a wider range of clinical HIC values at both 1.5 T and 3 T using monoexponential models. [17][18][19] To date, multispectral fat-water models have not been thoroughly investigated for estimating R 2 * in UTE acquisitions, except one study that incorporated an NLSQ multispectral model for R 2 * quantification using a three-dimensional (3D) UTE cones acquisition at 3 T. 20 However, this study involved only patients with mild to moderate iron overload (R 2 * < 550 s À1 ), and the NLSQ R 2 * results were not validated with any reference monoexponential fitting model or biopsy HIC values. A thorough and systematic investigation of the multispectral fat-water R 2 * models for different GRE and UTE acquisitions will be beneficial to assess their performances in estimating accurate R 2 * values under various hepatic iron overload conditions before clinical use.…”
Section: Introductionmentioning
confidence: 99%